KORELASI BEBERAPA KOMPONEN KIMIA TERHADAP PENILAIAN ORGANOLEPTIK DAN HARGA BERAS BERMEREK YANG BEREDAR DI KOTA DENPASAR (STUDI KASUS DI PASAR SWALAYAN KOTA DENPASAR) - Wrasiati, Luh Putu; Hartiati, Amna; Ummy Indiyani, Ni Kadek (Universitas Udayana, 2007)
The research aimed to (1) observe the correlation of chemical component rice brand with organoleptik of yielded rice test; (2) observe the correlation of chemical components with chosen price rice brand; (3) determine which component have the most effect on organoleptik test of yielded rice.This research used 6 (six) chosen rice brand which were taken from supermarket that located in Denpasar by using purposive sampling. Analyses covered chemical test and organoleptik test. Chemical test cover rate test of amylase, amilopektin, and water content, the test of organoleptik covered test of scoring for texture, test hedonic to feel and acceptance of entirety. The result of organoleptik test was analyzed with fragment test then acceptance mean is overall was test correlated with the result of chemical test and price mean of chosen rice.Result of acceptance mean of organoleptik overall data indicate that rice with Bengawan Super brand Sunflower was the most liked by consumers and brand C4 Super brand wasthe least taken by consumers. Result of chemical analysis indicate that the water rate of six rice brands pursuant to SNI 01-6128-1999 and rate of their pertained is lower until mean. This results indicated that the regression equation between overall acceptance, with amylase rate and water rate (Y/X1/X3) was Y = 114,924 + 1,308 X1 - 0,037 X12 - 23,121 X3 + 1,105 X32 which showed the correlation coefficient was 0,760 and coefficient of determinacy was 0,578. This correlation hasshowed strong level relation. Regression equation between chemical component and the price of brand rice have chosen was Y = 27791,960 - 13,810 X2 - 0,129 X22 - 3863,140 X3 + 175,691 X32 which showed the correlation coefficient is 0,984 and coefficient of determination was 0,967. This correlation has very strong relation. Chemical component which had the most effect to the texture was rate of amylase and amilopektin with strong relation level. Chemical component which had the most effect on rice and acceptance of entirety rate was taste amilopektin level.